Characterization of Submesoscale Turbulence in the East/Japan Sea Using Geostationary Ocean Color Satellite Images - J. Choi; Y.‐G. Park; W. Kim; Y. H. Kim (Geophysical Research Letters)
Abstract Submesoscale processes are key in understanding physical and biological phenomena near the surface, but there remains a lack of observational evidence over large areas. We used hourly images from a geostationary satellite that can resolve variation in surface ocean color over an area of few hundred kilometers. The temporal variation in the surface chlorophyll a distribution captured by the satellite images was first used to generate a submesoscale‐permitting velocity field, from which we calculated the turbulence statistics such as kinetic energy spectra, velocity structure functions, and energy flux. Application to the April scenes in the East/Japan Sea showed that the kinetic energy spectra had a transition scale at 50 km that suggested two spectral regimes following k−3 and k−5/3, implying the coexistence of quasi‐geostrophic turbulence and surface quasi‐geostrophic turbulence. The chlorophyll a scalar spectrum suggested two spectral regimes of k−5/3 and k−1 with a transition at 3 km.